Seismic structural study of Mishrif and Nahr Umr Formations in Huwaiza oilfield south-eastern Iraq - Abd Al-Ridha, Nawal; Yousif, Hayder Mohammed (Iraqi Journal of Science, 2019)
An interpretive study of two-dimension seismic data of the Huwaiza oilfield was carried out using Petrel 2015 program. Twenty seismic section were used, these seismic sections were carried out at three-time stages: HH survey in 1976, 2HH survey in 1978 and AM in 1980. Mishrif and Nahr Umr reservoirs were selected to study because they are the most important reservoirs in the neighbor fields. The study showed that the structure is an anticline trending North-South, so that the field may belong to Zubair tectonic subzone rather than Tigris subzone, which is northwest-southeast trending. A hypothetical model was drawn up showing the extension of the field in the Iraqi and Iranian territories based on information from both sides, it showed that the field is an extension of the large Iranian field called Azadegan and that Iraq has a small part of it, also the model illustrated that what is called south Huwaiza is the north-western part of Azadegan.